Enlightenment Orientalism in the American Mind, 1770-1807 - Pangborn, Matthew H., author.
1 online resource (282 pages)
Keywords: This study engages with the emerging field of energy humanities to provide close readings of several early American oriental-observer tales. The popular genre of orientalism offered Americans a means to critique new ideas of identity, history, and nationality accompanying protoindustrialization and a growing consumerism. The tales thus express a complex self-reflection during a time when America’s exploitation of its energy resources and its engagement in a Franco-British world-system was transforming the daily life of its citizens. The genre of the oriental observer, this study argues, offers intriguing glimpses of a nation becoming strange in the eyes of its own inhabitants.